Birth incidence, deaths and hospitalisations of children and young people with Down syndrome, 1990–2015: birth cohort study. Issue 4 (1st April 2020) - Hughes-McCormack, Laura Anne; McGowan, Ruth; Pell, J P; Mackay, Daniel; Henderson, Angela; O'Leary, Lisa; Cooper, Sally-Ann
Abstract : Objective: To investigate current Down syndrome live birth and death rates, and childhood hospitalisations, compared with peers. Setting: General community. Participants: All live births with Down syndrome, 1990–2015, identified via Scottish regional cytogenetic laboratories, each age–sex–neighbourhood deprivation matched with five non-Down syndrome controls. Record linkage to Scotland's hospital admissions and death data. Primary outcome: HRs comparing risk of first hospitalisation (any and emergency), readmission for children with Down syndrome and matched controls were calculated using stratified Cox proportional hazards (PH) model, and length of hospital stay was calculated using a conditional log-linear regression model. Results: 689/1479 (46.6%) female and 769/1479 (51.9%) male children/young people with Down syndrome were identified (1.0/1000 births, with no reduction over time); 1235 were matched. 92/1235 (7.4%) died during the period, 18.5 times more than controls. More of the Down syndrome group had at least one admission (incidence rate ratio(IRR) 72.89 (68.72–77.32) vs 40.51 (39.15–41.92); adjusted HR=1.84 (1.68, 2.01)) and readmissions (IRR 54.85 (51.46–58.46) vs 15.06 (14.36–15.80); adjusted HR=2.56 (2.08, 3.14)). More of their admissions were emergencies (IRR 56.78 (53.13–60.72) vs 28.88 (27.73–30.07); first emergency admission adjusted HR=2.87 (2.61, 3.15)). Children with Down syndrome had 28% longer first admission after birth. Admission rate increased from 1990–2003 to 2004–2014 for the Down syndrome group (from 90.7% to 92.2%) and decreased for controls (from 63.3% to 44.8%). Conclusions: We provide contemporaneous statistics on the live birth rate of babies with Down syndrome, and their childhood death rate. They require more hospital admissions, readmissions emergency admissions and longer lengths of stays than their peers, which has received scant research attention in the past. This demonstrates the importance of statutory planning as well as informal support to families to avoid added problems in child development and family bonding over and above that brought by the intellectual disabilities associated with Down syndrome.